Organizational Behavior and Its Impact on Bank Performance : An Analytical Study on A Sample of Iraqi Banks - أحمد عمار إلياس (PROSPECTIVE RESEARCHES, 2024)
The research aims to understand organizational behavior and its impact on the performance of financial institutions. It also seeks to identify positive organizational behavior factors and their influence on financial performance, shedding light on the role of organizational behavior and its impact on financial institution performance. The significance of this research lies in the multidimensional and complex nature of organizational behavior, which is challenging to explain and define within a single scientific discipline. This necessitates the integration of various humanities disciplines to achieve a high level of precision in understanding organizational behavior.The research is based on a fundamental hypothesis that there is a statistically significant relationship between dimensions of organizational behavior and dimensions of financial performance. The research sample comprises financial institutions in Baghdad, including Al-Ahli Bank. The researcher employed a field study approach, conducted data analysis, and tested hypotheses using appropriate statistical methods, utilizing functions within the SPSS statistical package. The research yielded several conclusions, with one of the most notable being that organizational behavior contributes to enhancing financial institution performance, playing a significant and effective role. Furthermore, the research identified a strong correlational relationship and impact between the study's variables.